3D Scanning of naturally corroded steel bars. An assessment of corrosion behaviour and correlations to critical cross-sections - Das, Priyanka (My University, 2025)
The present study focuses on the effect of corrosion of steel reinforcement in reinforced concrete (RC) structures. Corrosion has a large impact on the structural performance of RC structures. A cross-section reduction of the steel bar occurs due to the oxidation of steel which unequivocally convey a non-uniform distribution of pits along the bar length. For a specific length, it is possible to identify a critical cross-section (CCS), which attains the highest loss of area. This thesis defines CCS and illustrates how the different characterizing parameters of the same can be described from the measured average corrosion level of a specific bar length. To cover this objective naturally corroded steel bars from a real bridge situated in Stallbacka were employed. After structural testing of the edge beams of the bridge, the steel reinforcement was extracted, cut into suitable lengths, and subsequently cleaned. Thereafter the average corrosion level of each specific bar was obtained by using two different techniques, gravimetric and 3D scanning. By weight loss method accurate measurements of the average corrosion level were obtained; by 3D scanning discrete corrosion level in each cross-section was quantified. In addition, variables such as pit depth, pit length, pit width, and, corroded perimeter, were measured from the CCS by combined physical and numerical post-processing of the 3D scanning techniques. These measurements led to a precise description of the CCS. Finally, relations between all the measured parameters to the average corrosion level were obtained, hence possible predictions of the CCS from the estimated average corrosion level of a specific bar length could be described. Furthermore, in further works, the tensile properties of the utilized steel bars can be correlated to the CCS description and later estimate the reduction of capacity of the steel bars because of the presence of corrosion.
Keywords: Steel reinforcement, reinforced concrete structures, corrosion, structural performance, cross-section reduction, oxidation of steel, non-uniform distribution of pits, the highest loss of area, structural testing of the edge beams, average corrosion level, gravimetric and 3D scanning, pit depth, pit length, pit width and, corroded perimeter, post-processing, reduction of capacity of the steel bars